Bridging Between Cultural Heritage Institutions 9th Italian Research Conference, IRCDL 2013, Rome, Italy, January 31 -- February 1, 2013. Revised Selected Papers - Catarci, Tiziana; Ferro, Nicola; Poggi, Antonella (Communications in Computer and Information Science, 2014)
This book constitutes the thoroughly refereed proceedings of the 9th Italian Research Conference on Digital Libraries, held in Rome, Italy, in January/February 2013. The 18 full papers presented together with an invited paper and a panel paper were selected from extended versions of the presentations given at the conference. The papers then went through an additional round of reviewing and revision after the event. The papers are organized in topical sections on information access; Digital Library (DL) architecture; DL projects; semantics and DLs; models and evaluation for DLs; DL applications; discussing DL perspectives.